2010
DOI: 10.14295/bds.2007.v10i3.272
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of anionic collagen matrices and its influence on the orientation of cellular growth.

Abstract: This study aimed to analyze the biocompatibility of anionic collagen matrices, the local bone response following implantation in surgically-created bone defects, and also the influence of the collagen fiber orientation on the neoformed osseous tissue. Seventy two rats (Rattus norvegicus albinus) were used in this experiment. The animals were divided into four experimental groups: Group 1 (control), without implants; Group 2, pericardium medullar implants 12 hours; Group 3, medullar implants of tendon 24 hours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…Regarding the percentage of biomaterial, there was no statistical difference between the groups in the two analysis periods (14 vs. 42 days) except for G2/BFB due to the higher rate of resorption of the biomaterial. The other groups showed a small variation in the volumetric density of bone matrix particles [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the percentage of biomaterial, there was no statistical difference between the groups in the two analysis periods (14 vs. 42 days) except for G2/BFB due to the higher rate of resorption of the biomaterial. The other groups showed a small variation in the volumetric density of bone matrix particles [ 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its indications are in medical, veterinary and dental practice, due to the possibility of personalized formulation and replacement of conventional sutures. Considering all of the properties described for this bioproduct, which go beyond the adhesive capacity, the name “sealant” was reconsidered, and it has recently been called “fibrin biopolymer” [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cellular behavior agrees with studies that reported as a critical-size bone defect, since the lack of growth and nutrition factors at the center of the surgical area limits osteoblastic differentiation, facilitating the growth of fibroblasts [ 28 , 70 ]. In the same period, the BT and BTP groups presented inflammatory cells involving the xenograft particles, a cellular mechanism inherent to the implantation of biomaterials in tissues in vivo [ 71 , 72 ]. However, this biological response did not elicit an intense inflammatory reaction that could compromise the entire surgical procedure.…”
Section: Discussionmentioning
confidence: 99%